Phytochemical profiles, anti-asthmatic and immunomodulatory effects of lignosus rhinocerus in airway inflammation model - Malagobadan, Johnathan A/L (2016)
Lignosus rhinocerus (L. rhinocerus) or locally known as Tiger’s Milk mushroom, is traditionally used in the treatment of various diseases including asthma by indigenous communities in Malaysia. However, to date, its efficacy on asthma and its immunomodulating potential have not been confirmed by scientific studies. Also, there is sparse information available on its active constituents. This study investigated volatile constituents of hot water extract (HWE), cold water extract (CWE) and crude (CRD) L. rhinocerus using gas chromatography mass spectrometry (GC-MS). The anti-asthmatic potential of L. rhinocerus extracts was investigated on ovalbumin (OVA)-induced airway inflammation Sprague Dawley rats. Immunomodulatory effects of L. rhinocerus were carried out in BALB/c mice. Sequential extractions of L. rhinocerus using five solvents (petroleum ether, diethyl ether, hexane, ethyl acetate and methanol) were conducted prior to GC-MS analysis. Overall, 44 constituents were identified from CRD L. rhinocerus. Compounds from the fatty acid group were the most predominant (68.58%) and the main constituent was linoleic acid (49.39%). GC-MS analysis of HWE L. rhinocerus identified 18 constituents with the main compound also linoleic acid (21.35%). In contrast, CWE only demonstrated the presence of methylcyclopentane (97.74%) and cyclohexane (2.26%). Male Sprague Dawley rats were sensitized with two intraperitoneal injections of 10 mg/ml OVA emulsified in 100 mg/ml aluminium hydroxide with the presence of 50 ng/ml of Bordetella pertussis, on days 0 and 14 followed by treatment with L. rhinocerus extracts on day 21 for 7 days. Optimization study indicated optimized dosage for L. rhinocerus HWE was 500 mg/kg, CWE (250 mg/kg) and CRD (250 mg/kg). Treatments with L. rhinocerus extracts significantly ameliorated related asthmatic parameters in the induced rats. Specifically, HWE comparatively reduced eosinophils numbers in BALF, IgE in serum, Th2 cytokines (IL-4, IL-5 and IL-13) levels in BALF, and eosinophil infiltrations in the lungs than the CWE and CRD. Flow cytometry analysis revealed HWE to reduce eosinophils and improved T regulatory cells compared to CRD and CWE. A total of 21 asthma related genes were successfully down-regulated with HWE treatment. Immunomodulatory effects of HWE were studied in in vitro and in vivo model. Treatment with HWE L. rhinocerus extract demonstrated improved splenocyte population mainly of CD3+CD4+ and CD3+CD8+ when compared with untreated mice groups. This study also demonstrated improved splenocytes proliferation and phagocytosis activity and controlled NO production. In conclusion, L. rhinocerus has the potential to be used as an alternative for the treatment of allergic asthma.